Anglo-Saxon saints' lives as history writing in late medieval England - Camp, Cynthia Turner (D. S. Brewer, 2015)
Edith of Wilton and the writing of women's history -- Audrey abroad : spiritual and genealogical filiation in the middle English lives of Etheldreda -- Henry Bradshaw's Life of Werburge and the limits of holy incorruption -- The limits of narrative history in the written and pictorial lives of Edward the Confesor -- The limits of poetic history in Lydgate's Edmund and Fremund and the Harley 2278 pictorial cycle